Восстановление подшипниковых узлов скольжения полиамидоэпоксидными композиционными материалами - Малай, Л. Г.; Горобец, В. Ф.; Попескул, А. Т.; Malai, L.; Gorobet, V.; Popescul, A. (ЦНТУ, 2019)
Целью работы явлляется изучение трибологического поведения полиамидоэпоксидных композиционных материалов (ПЭКМ), в зависимости от концентрации отдельных компонентов. В качестве объекта исследования были выбраны трибологические пары металл–ПЭКМ, наполненные стеклянными микросферами и другими материалами. Мета роботи полягає у вивченні трибологічної поведінки поліамідоепоксидних композиційних матеріалів (ПЕКМ), в залежності від концентрації окремих компонентів. В якості об’єкта досліджень були обрані трибологічні пари метал–ПЕКМ, які наповнені скляними мікросферами та іншими матеріалами. The reliability, productivity and competitiveness of agricultural machinery, as well as related industries, is largely determined by the resource of sliding bearing units, which during operation are influenced by many adverse factors such as: high dust content, bad weather, temperature fluctuations, high humidity, aggressive medium, uneven loads, mechanical shocks, vibrations and shock loads, insufficient lubrication, etc. Therefore, the development and implementation of new materials for the restoration of sliding bearing units capable of working in such conditions is quite relevant and is of interest to science and practice in the field of technical service of agricultural machinery. Tribological tests were carried out on a universal tribometer UMT–2 using a special module for the pin–disk friction pairs. Visualization and recording of research results were carried out using a special program. The deviation of the location of the corresponding surfaces does not exceed 25% of the size tolerance of the corresponding surfaces. The studies were carried out under the following conditions: pressure 1 MPa, sliding speed 1,5 m/s, radius from the centre of the disk to the axis of sample 40 mm, Litol 24 was used as a lubricant. The proposed composite material as a matrix contains PA–12 polyamide (OST 6–05–425) – 70% and the epoxy oligomer P–EP.534 (TU 6–10–189–83) – 30%, and as fillers: molybdenum disulfide DM–1 (TU 48–19–133–90), hollow glass microspheres MS–VP gr. 5–4% and basalt fibre. The composite material was applied by hot pressing to one of the ends of the pins made of ordinary carbon steel without heat treatment. Studies on optimizing the composition of PECM were carried out using mathematical planning of experiments, namely, a 3–factor non–compositional plan of the Box–Benkin type. The obtained data were processed using the STATGRAPHICS program. An analysis of the equation shows that all factors contribute to a decrease in the coefficient of friction of the polyamide epoxy composition with steel (b1, b2 and b3, have negative values). Molybdenum disulfide, then glass microspheres and, finally, basalt microfiber (|b1|>|b2|>|b3|) most affects the coefficient of friction. The value of the optimal coefficient of friction (K=0,115). The values of these factors in coded coordinates are 5% – molybdenum disulfide, 23% – hollow glass microspheres and 4,31% – basalt microfiber from the composition. Based on the results of the studies, the following conclusions can be drawn: tribological monitoring of laboratory samples from composite polyamide–epoxy materials tested on carbon steel disks using LITOL lubricant showed a beneficial effect of all components of the composition on the friction coefficient; The results obtained made it possible to determine the optimal composition of PECM, at which the lowest coefficient of friction was achieved (K=0,115).
Відновлення підшипникових вузлів ковзання поліамідоепоксидними композиційними матеріалами
Restoration of Sliding Bearing Units With Polyamide–epoxy Composite Materials
Keywords: базальтовое волокно; коэффициент трения; стеклянные микросферы; дисульфид молибдена; Полиамид–12; базальтове волокно; коефіцієнт тертя; скляні мікросфери; дісульфид молібдену; Поліамід–12; basalts microfibres; friction coefficient; glass microspheres; moliybdenum disulfide; Polyamide PA12